Method for preparing anisotropic neodymium-iron-boron magnet thin-wall ring through high-energy rays
Through high-energy ray irradiation treatment and epoxy resin coating technology, the problem of the inability to quickly prepare thin-wall rings of high-strength anisotropic neodymium iron boron magnets in the prior art is solved, and the thin-wall ring samples with rapid curing and high magnetic properties are achieved.
Patent Information
- Application Number
- CN202411750039.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The prior art cannot quickly prepare high-strength anisotropic neodymium iron boron magnet thin-wall rings, and traditional methods require long-term baking and secondary processing, making it difficult to meet the demand for rapid curing of thin-wall magnets.
High-energy ray irradiation treatment combined with epoxy resin coating technology is used to significantly improve the cross-linking degree of epoxy resin through high-energy rays, shorten the curing time, and prevent powder oxidation during the magnetic alignment process, and maintain the magnetic properties of the material.
It realizes the rapid preparation of high-strength thin-walled ring samples, shortens the curing time, maintains the magnetic properties of the material, and ensures the magnetic index and mechanical strength of the final product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth magnetic materials, in particular to a method for preparing anisotropic NdFeB magnet thin-walled rings by using high-energy rays. Background Art
[0002] NdFeB is the permanent magnet material with the best magnetic properties currently. It usually contains about 30% of rare earth elements such as neodymium (Nd) and praseodymium (Pr). It is widely used in the fields of automobiles, industrial automation, consumer electronics, and household appliances. It has important application value in micro motors with power ranging from a few watts to several hundred watts.
[0003] In recent years, 3D printing technology has made great progress and has been widely used in the processing of metals, polymers and inorganic non-metallic materials. This technology can not only produce complex and special-shaped parts, but also overcome the problems of long cycle and high cost in the traditional mold opening process. It is also particularly suitable for small batch and multi-variety production needs. However, the current magnetic materials used in motors have a wide variety of specifications. If a separate mold is opened for each size, it will lead to high costs and a long cycle.
[0004] Although existing 3D printing technologies, such as powder-sintering molding, printing wire laying process, slurry-sintering process, etc., have studied the rapid moldless 3D molding of NdFeB and its powder, these methods have not yet fully demonstrated the unique properties of HDDR anisotropic magnetic powder. First, the existing 3D printing methods often require subsequent secondary processing to meet the requirements of installation testing. Secondly, the bonding process of anisotropic magnets allows their magnetic energy product to reach 12-20MGOe at the same size, while the maximum magnetic energy product of isotropic magnetic powder is only 12MGOe, showing its superiority in specific sizes (especially thin-walled circular ring parts). Thirdly, 3D powders need to be ball milled and sintered in the later stage, which has limitations in the preparation process.
[0005] Traditional UV 3D molding methods cannot meet the needs of rapid solidification of thin-walled magnets due to their weak energy and insufficient penetration, and still require long-term baking and secondary processing.
[0006] For example, patent CN102568730A discloses a high mechanical strength bonded NdFeB permanent magnet and a preparation method thereof, which has the aforementioned problems.
[0007] Therefore, it is particularly important to develop a rapid sample preparation process based on anisotropic magnetic powder and its composite materials. Summary of the invention
[0008] In view of this, the present invention aims to propose a method for preparing anisotropic NdFeB magnet thin-walled rings using high-energy rays to solve the problem that anisotropic NdFeB magnet thin-walled rings cannot be quickly prepared in the prior art.
[0009] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0010] A method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays comprises the following steps: mixing epoxy resin with a solvent to prepare a uniform solution, immersing 20 parts of anisotropic NdFeB magnetic material powder into the solution, adding 0.05 parts of a curing agent, and after the solvent is completely evaporated, obtaining anisotropic NdFeB magnetic material powder coated with epoxy resin, dry-mixing 9.9 parts of anisotropic NdFeB magnetic material powder coated with epoxy resin with 0.1 parts of triallyl isocyanurate to obtain a mixed powder, heating the mixed powder to 80°C, extruding the mixed powder through an extruder to prepare a thin-walled ring, placing the thin-walled ring in a pulsed magnetic field with an intensity of 2T for magnetic field orientation, placing the oriented thin-walled ring in a high-energy ray irradiation device for irradiation treatment, and curing the thin-walled ring.
[0011] The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays described in the present application uses high-energy ray irradiation treatment, which can significantly improve the cross-linking degree of epoxy resin and shorten the curing time. Compared with traditional baking and secondary processing, high-strength thin-walled ring samples can be quickly prepared. At the same time, high-energy ray irradiation can effectively prevent oxidation of powder during magnetic alignment, maintain the magnetic properties of the material, and ensure the magnetic indicators of the final product. By coating the anisotropic NdFeB magnetic material powder with epoxy resin, the lubricity of the powder can be improved, friction during processing can be reduced, and the quality of the product can be improved.
[0012] Further, 1 part of epoxy resin is mixed with 4 parts of solvent to prepare a uniform solution, and the solvent is acetone.
[0013] This setting can significantly reduce the viscosity of the epoxy resin, improve its fluidity, make it easier to mix evenly with the anisotropic NdFeB magnetic material powder, and ensure the uniformity and consistency of the finished product. The use of solvents can improve the wettability of the epoxy resin to the anisotropic NdFeB magnetic material powder, ensuring that the powder is fully coated, thereby improving the mechanical strength and magnetic properties of the final product. Acetone is a highly volatile solvent that can evaporate in a shorter time, shortening the production cycle.
[0014] Furthermore, the anisotropic NdFeB magnetic material is processed by a HDDR furnace, and then the anisotropic NdFeB magnetic material is crushed by a wheel mill to obtain anisotropic NdFeB magnetic material powder with a particle size of 30-100 μm.
[0015] HDDR (high temperature annealing and magnetic field orientation) furnace treatment can improve the crystal structure and magnetic orientation of NdFeB materials, enhance their magnetic properties, and make the final powder have higher coercive force and maximum magnetic energy product. Through the wheel mill crushing treatment, the particle size of the powder can be controlled within the range of 30-100μm, ensuring that the particle size distribution of the powder is uniform, which is helpful for subsequent processing and application, and improves the consistency and performance of the finished product.
[0016] Furthermore, the initial magnetic properties of the anisotropic NdFeB magnetic material powder are Hcj=13kOe, (BH)max=38MGOe.
[0017] This setting gives the material a strong anti-magnetization ability. When the external magnetic field is removed, the material can maintain its magnetism. The high magnetic energy product allows less material to provide strong magnetic force, effectively reducing the size and weight of the motor.
[0018] Furthermore, the irradiation dose in the high-energy ray irradiation device is 30 kG, and the irradiation time is 15 minutes.
[0019] This setting can effectively accelerate the cross-linking reaction of epoxy resin and increase the curing speed. High-energy ray irradiation can prevent the oxidation of powder during the alignment and curing of magnetic materials to a certain extent, maintain the magnetic and chemical stability of the material, and ensure the quality of the final product. Irradiation treatment can also improve the lubricity of powder particles, reduce friction during the molding process, ensure the fluidity of powder during mixing and pressing, and improve molding efficiency.
[0020] Further, 1 part of epoxy resin is mixed with 3.5 parts of solvent to prepare a uniform solution, and the solvent is acetone.
[0021] This setting can significantly reduce the viscosity of the epoxy resin, improve its fluidity, make it easier to mix evenly with the anisotropic NdFeB magnetic material powder, and ensure the uniformity and consistency of the finished product. The use of solvents can improve the wettability of the epoxy resin to the anisotropic NdFeB magnetic material powder, ensuring that the powder is fully coated, thereby improving the mechanical strength and magnetic properties of the final product. Acetone is a highly volatile solvent that can evaporate in a shorter time, shortening the production cycle.
[0022] Furthermore, it also includes SmFeN powder. The anisotropic NdFeB magnetic material is processed by a HDDR furnace, and the anisotropic NdFeB magnetic material and SmFeN material are crushed by a wheel mill to obtain anisotropic NdFeB magnetic material powder and SmFeN powder with a particle size of 30-100μm. 80 parts of anisotropic NdFeB magnetic material powder are mixed with 18 parts of SmFeN powder to form a composite powder.
[0023] Mixing anisotropic NdFeB magnetic materials and SmFeN materials can achieve complementary performance and enhance the overall magnetic properties of the composite powder. At the same time, due to the low price of SmFeN materials, costs can be reduced. SmFeN materials have good antioxidant properties and can improve the corrosion resistance of composite materials to a certain extent and extend the service life of the materials.
[0024] Furthermore, the initial magnetic properties of the anisotropic NdFeB magnetic material powder are Hcj=14kOe, (BH)max=39MGOe, and the initial magnetic properties of the SmFeN powder are Br=1.3-1.5T, (BH)max=38-40MGOe.
[0025] This setting enables the anisotropic NdFeB magnetic material powder to have a higher magnetic energy product, and less material can provide strong magnetic force. The SmFeN powder can maintain good magnetic properties at high temperatures and is suitable for applications in high temperature environments. The addition of SmFeN material helps to reduce the risk of demagnetization under high temperature or high load conditions, enhances the anti-demagnetization ability of the composite material, and enables the final product to maintain good performance under different working conditions.
[0026] Furthermore, the irradiation dose in the high-energy ray irradiation device is 15 kG, and the irradiation time is 10 minutes.
[0027] Shorter irradiation time can significantly improve production efficiency, making the curing process of thin-walled rings faster and responding quickly to market demand. High-energy ray irradiation can effectively prevent oxidation of powder during the alignment of magnetic materials, maintain the magnetic properties of the material, and avoid performance degradation caused by oxidation.
[0028] Furthermore, the thin-walled ring has an inner diameter of 10 mm, an outer diameter of 12 mm, a height of 2.0 mm, and a thickness of 1.0 mm.
[0029] This design can optimize the magnetic field distribution, improve the magnetic properties of the thin-walled ring, and reduce the overall weight of the thin-walled ring, thereby improving energy efficiency.
[0030] Compared with the prior art, the method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays described in the present invention has the following advantages:
[0031] 1) Using high-energy ray irradiation treatment can significantly increase the cross-linking degree of epoxy resin, shorten the curing time, and quickly prepare high-strength thin-walled ring samples;
[0032] 2) High-energy ray irradiation can effectively prevent the oxidation of powder during the magnetic alignment process, maintain the magnetic properties of the material, and ensure the magnetic indicators of the final product. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0034] Example 1
[0035] A method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays, wherein anisotropic NdFeB magnetic materials are processed by an HDDR furnace, and then crushed by a wheel mill to obtain anisotropic NdFeB magnetic material powder (HDDRNd-Fe-B) with a particle size of 30-100 μm, and the initial magnetic properties are Hcj=13kOe, (BH)max=38MGOe, 1 part of epoxy resin is mixed with 4 parts of solvent to prepare a uniform solution, 20 parts of anisotropic NdFeB magnetic material powder are immersed in the solution, 0.05 parts of curing agent are added, and after the solvent is completely evaporated, anisotropic NdFeB magnetic material powder coated with epoxy resin is obtained. The epoxy resin, solvent, anisotropic NdFeB magnetic material powder and curing agent are all measured by weight.
[0036] Preferably, the solvent is acetone.
[0037] 9.9 parts of anisotropic NdFeB magnetic material powder and 0.1 parts of triallyl isocyanurate are dry-mixed. Here, the anisotropic NdFeB magnetic material powder after drying is used. The mixed powder is heated to 80°C and extruded through an extruder to form a thin-walled ring with an inner diameter of 10 mm, an outer diameter of 12 mm, a height of 2.0 mm and a thickness of 1.0 mm. Then, magnetic field orientation is carried out in a 2T pulsed magnetic field. The oriented thin-walled ring is placed in a high-energy ray irradiation device and irradiated at an energy of 30 kGy for 15 minutes to solidify the thin-walled ring.
[0038] The anisotropic NdFeB magnet prepared by the above method has Hcj=12.8kOe and (BH)max=17MGOe. The use of high-energy ray irradiation not only increases the crosslinking degree of the epoxy resin and improves the lubricity of the powder particles, but also effectively prevents oxidation of the powder during the magnetic alignment process.
[0039] The preparation method of this embodiment can save time in making precision molds and quickly provide samples with higher performance indicators in the stage of rapid response to customer needs, and BHmax = 13-17MGOe, which is a performance that is not achieved by isotropic NdFeB materials. In addition, due to the high resin content, it has good thermal corrosion resistance. The use of high-energy ray curing method shortens the curing time, increases the curing speed, and improves the forming rate of the product.
[0040] Example 2
[0041] The anisotropic NdFeB magnetic material is processed by a HDDR furnace, and then the anisotropic NdFeB magnetic material and SmFeN material are crushed by a wheel mill to obtain anisotropic NdFeB magnetic material powder and SmFeN powder with a particle size of 30-100μm, whose initial magnetic properties are Hcj=14kOe, (BH)max=39MGOe, SmFeN powder, Br=1.3-1.5T, (BH)max=38-40MGOe, and 80 parts of anisotropic NdFeB magnetic material powder are mixed with 18 parts of SmFeN powder to prepare a composite powder.
[0042] Preferably, anisotropic NdFeB magnetic material powder, SmFeN, SmCo and FeO are mixed to prepare composite powder.
[0043] Mix 1 part of epoxy resin with 3.5 parts of solvent to make a uniform solution, immerse 20 parts of composite magnetic powder in the solution, add 0.05 parts of curing agent, and after the solvent is completely evaporated, obtain epoxy resin-coated NdFeB composite powder with no acetone residue. Epoxy resin, solvent, anisotropic NdFeB magnetic material powder, SmFeN powder, and curing agent are all calculated by weight.
[0044] Preferably, the solvent is acetone.
[0045] 9.9 parts of NdFeB composite powder and 0.1 parts of triallyl isocyanurate are dry-mixed. Here, the dried NdFeB composite powder is used. The mixed powder is heated to 80°C and extruded through an extruder to form a thin-walled ring with an inner diameter of 10 mm, an outer diameter of 12 mm, a height of 2.0 mm, and a thickness of 1.0 mm. Then, magnetic field orientation is carried out in a 2T pulsed magnetic field. The oriented thin-walled ring is placed in a high-energy ray irradiation device and irradiated at an energy of 15 kGy for 10 minutes to solidify the thin-walled ring.
[0046] The anisotropic NdFeB magnet composite material prepared by the above method has Hcj=13.6kOe and (BH)max=12MGOe. The use of high-energy ray irradiation not only increases the crosslinking degree of the epoxy resin and improves the lubricity of the powder particles, but also effectively prevents oxidation of the powder during the magnetic alignment process.
[0047] The preparation method of this embodiment can save the time of opening precision molds in the stage of quickly responding to customer needs, and quickly provide samples with higher performance indicators, and BHmax = 12MGOe. Although isotropic NdFeB materials with higher grades can also achieve this, this embodiment has a lower magnetic material cost due to the addition of SmFeN powder, and the resin content is higher, which has better thermal corrosion resistance. The product of this embodiment has more advantages under the same performance. In the prior art, once the size required by the customer changes, the mold must be re-opened. This magnetic thin-walled ring requires a high-precision mold, which takes a lot of time and economic costs, and cannot quickly respond to customer needs.
[0048] The anisotropic magnetic material and its composite powder described in this application can fill the performance gap between isotropic NdFeB and sintered NdFeB, forming a complete performance system, which can make the motor smaller and save rare earth usage, so there is a huge market demand.
[0049] The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays described in the present application has the following advantages: the use of high-energy rays improves the curing speed of the anisotropic NdFeB magnet thin-walled rings during molding, shortens the curing time, and can quickly prepare high-strength thin-walled magnetic ring samples.
[0050] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays, characterized in that: Epoxy resin and solvent are mixed to prepare a uniform solution, 20 parts of anisotropic NdFeB magnetic material powder are immersed in the solution, 0.05 parts of curing agent are added, and after the solvent is completely evaporated, epoxy resin-coated anisotropic NdFeB magnetic material powder is obtained, and then 9.9 parts of epoxy resin-coated anisotropic NdFeB magnetic material powder are dry-mixed with 0.1 parts of triallyl isocyanurate to obtain a mixed powder, the mixed powder is heated to 80° C., and extruded through an extruder to form a thin-walled ring, the thin-walled ring is placed in a pulsed magnetic field with an intensity of 2T for magnetic field orientation, the oriented thin-walled ring is placed in a high-energy ray irradiation device for irradiation treatment, and the thin-walled ring is cured.
2. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 1, characterized in that: Mix 1 part epoxy resin with 4 parts solvent to make a uniform solution. The solvent is acetone.
3. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 2, characterized in that: The anisotropic NdFeB magnetic material is processed by using a HDDR furnace, and then the anisotropic NdFeB magnetic material is crushed by using a wheel mill to obtain anisotropic NdFeB magnetic material powder with a particle size of 30-100 μm.
4. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 3, characterized in that: The initial magnetic properties of the anisotropic NdFeB magnetic material powder are Hcj=13kOe, (BH)max=38MGOe.
5. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 4, characterized in that: The irradiation dose in the high-energy ray irradiation device is 30 kG, and the irradiation time is 15 minutes.
6. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 1, characterized in that: Mix 1 part of epoxy resin with 3.5 parts of solvent to make a uniform solution. The solvent is acetone.
7. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 6, characterized in that: It also includes SmFeN powder. The anisotropic NdFeB magnetic material is processed by a HDDR furnace, and the anisotropic NdFeB magnetic material and SmFeN material are crushed by a wheel mill to obtain anisotropic NdFeB magnetic material powder and SmFeN powder with a particle size of 30-100μm. 80 parts of anisotropic NdFeB magnetic material powder are mixed with 18 parts of SmFeN powder to form a composite powder.
8. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 7, characterized in that: The initial magnetic properties of the anisotropic NdFeB magnetic material powder are Hcj=14kOe, (BH)max=39MGOe, and the initial magnetic properties of the SmFeN powder are Br=1.3-1.5T, (BH)max=38-40MGOe.
9. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 8, characterized in that: The irradiation dose in the high-energy ray irradiation device is 15 kG, and the irradiation time is 10 minutes.
10. The method for preparing anisotropic NdFeB magnet thin-walled rings by high-energy rays according to claim 1, characterized in that: The thin-walled ring has an inner diameter of 10 mm, an outer diameter of 12 mm, a height of 2.0 mm and a thickness of 1.0 mm.
Citation Information
Patent Citations
High mechanical strength bonding neodymium iron boron permanent magnet and preparation method thereof
CN102568730A
Radiation-curing type magnetic coating and magnetic recording medium obtained by using same coating
JP1992004269A
Anisotropic magnet power compound, its manufacturing method and manufacturing method of anisotropic bond magnet using the same
JP2001068313A
METHOD OF MANUFACTURING Sm2Fe17N3 / Nd2Fe14B ANISOTROPIC COMPOSITE MAGNET
JP2007088354A
Composition for resin bond type magnet, magnetically anisotropic bond magnet using the same, and manufacturing method thereof
JP2007250577A